Analysis the implementation of the halal logo in the food industry in Malaysia / Nur Afini Abu Bakar and Azri Bhari - Abu Bakar, Nur Afini; Bhari, Azri (Academy of Contemporary Islamic Studies (ACIS), 2021)
The Halal logo acts as a stamp of approval for the legality of products on the market. The installation of this type of certificate has benefited Muslim consumers since it provides them confidence in consuming products that bear the emblem, which acts as verification of the product's legitimacy. The objective of this research to identify the requirements for the halal logo in the food industry in Malaysia and to analyzing non -compliance with halal logos in the food industry. The research methodology used in this study through qualitative methods. This study was conducted using qualitative research, using library and using observation method to collect data. Data were analyzed using inductive, deductive and comparative methods on the topic material being discussed. The finding shows that, important the Halal logo for food industry to understand about implementation of the halal logo in the food industry. Researcher hope that this research can assist the authorities towards improvement in to implementation of halal logo more effectively to ensure the issue about misuse of Halal logo can be addressed more effectively by all communities.